A facile approach towards amidinophenylalanine derivatives as building blocks for the synthesis of non-natural peptides and peptidomimetics - Behrouz, Somayeh; Kühl, Nikos; Klein, Christian D. (Tetrahedron letters, 2021)
The amidine function is extensively utilized as synthetic intermediate for structurally diverse heterocycles and as a core element in drugs and drug candidates. This study describes a facile and convenient approach for the highly efficient synthesis of amidinophenylalanine derivatives via the reduction of amidoximophenylalanines in the presence of Ac2O/AcOH/Zn at room temperature. The described process is attractive for process and medicinal chemistry due to its facility, safety, low cost, applicability for hydrogenation-sensitive compounds, and efficiency. Using this method, amidinophenylalanine derivatives as building blocks for peptides were obtained in excellent yields.
Gesehen am 26.11.2021